Leadership, social determinants of health and health equity: the case of Costa Rica - Epsy Campbell Barr; Michael Marmot (Pan American Health Organization, 2020)
Costa Rica has long been a country of special interest in the Americas and in global health because of its good health. The United Nations Development Programme ranks countries according to their level of human development based on life expectancy, education and national income. Although Costa Rica is ranked at 63 and classified as 'High', in terms of health it belongs in the 'Very High' group. In 2018 mean life expectancy for the 'Very High' countries was 79.5, while in Costa Rica it was 80. In 2018, under five mortality was 8.8/1000 live births, lower than countries ranked in the 'Very High' human development group. Expected years of schooling in Costa Rica is 15.4, closer to the average, 16.4 years, of the 'Very High' human development group than the average of the 'High' group. The country is much healthier than would be predicted by its national income; rather, other features of society's development are likely to have played a key role in the development of good health. These include (i) the decision to cease investment in national defence, which freed up money to invest in health, education and the welfare of the population; (ii) the decision to create a universal health system financed by the State, employers and workers in the 1940s; and (iii) the educational system, that generated opportunities to lift important sectors of the population out of poverty, allowing them to have basic sanitary conditions that increase their possibilities to live longer and in better conditions. Despite these advances, inequalities in terms of income and social conditions persist, presenting challenges in the field of health, particularly for lower-income populations and those of African and indigenous descent. These inequalities must be addressed using decisions based on scientific evidence, a greater use of disaggregated data to reveal progress in addressing these inequalities, and with a broader articulation of the health sector with policies that act on the social determinants of health.